Callovian and Oxfordian (Jurassic) teuthids (Coleoidea, Cephalopoda) from Chile. (14th September 2016) - Riccardi, Alberto C.
Abstract: Coleoid specimens from the Jurassic of northern Chile are included in two different species of Trachyteuthis, i.e., T. covacevichi Fuchs and Schultze, 2008 and T. chilensis n. sp., and in a new genus and a new species, Pseudoteudopsis perezi n. gen. n. sp. The specimens described and figured are from two different areas in northern Chile. Those referred to Pseudoteudopsis perezi n. gen. n. sp. came from a locality north of Calama and are associated with ammonites indicating the lower Callovian uppermost bodenbenderi to lowermost proximum zones (≈ gracilis Standard Zone) of the Andean ammonite zonation. Those described as T. covacevichi and T. chilensis n. sp. came from the Cordillera de Domeyko, northeast of Taltal, and are associated with ammonites indicating the middle Oxfordian transversarium Zone.